Pediatric Microbial Keratitis: Identification of Clinical Biomarkers for Prognosis and Outcome of 218 Cases From 2009 to 2019. Issue 9 (22nd September 2022) - Di Zazzo, Antonio; Rajan, Mugundhan; Dureja, Rohit; Antonini, Marco; Kanduri, Vaibhav; Madduri, Bhagyasree; Mohan, Nitin; Mohamed, Ashik; Fernandes, Merle
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The aim of this study was to analyze the risk factors, microbiological profile, and treatment efficacy in pediatric microbial keratitis (MK) and to identify clinical biomarkers prognosticating outcome. Methods: A retrospective analysis was conducted from patients younger than 16 years with MK-excluding viral, marginal, or interstitial keratitis. Data pertaining to predisposing factors, symptom duration, prior treatment, ulcer characteristics, microbiological profile, time to resolution, and final outcome were recorded. Statistical analysis was performed. The mixed-effects linear regression model with random intercept was used to evaluate factors affecting time to resolution. Results: Among 218 episodes of 215 pediatric patients with MK, the geometric mean of central [median 3 mm, interquartile range (IQR) 1–4.3 mm] and peripheral ulcers (median 1 mm, IQR 1–2.5 mm) was significantly different ( P < 0.0001). Organisms identified were bacteria (56.9%), fungi (31.5%), and acanthamoebae (2.3%). Of 172 cases (78.8%), which resolved in a median resolution time of 22 days (IQR, 11–44 days), 107 (81.6%) with absent/negative microbiology healed on empirical therapy. On multivariate analysis, peripheral ulcers and geometric mean ulcer size affected time to resolution. Significantly higher percentage of eyes, which worsened or perforated, were on topical steroids compared with those which healed (31.8% vs. 9.2%, P = 0.0061). Conclusions: Good outcome even in culture negative cases suggests empirical therapy may be instituted for nonsevere peripheral pediatric MK; however, the importance of a microbiological workup cannot be underscored enough. Ulcer location and geometric mean size of ulcer may be used as clinical prognostic markers for resolution.